Criminological Study of Domestic Violence in Iran - Ziya, Rashin; Ahmadi, Ahmad (Jurnal Cita Hukum, 2020)
AbstractViolence against women is a common phenomenon and its widespread dimensions cause many personal and social losses to husband and wife, family and society. This research was conducted using the library method which aims to investigate violence against women in Iranian society with a criminological approach. Many women have traditionally been subjected to violence or do not realize that it is an act of violence, because the law does not criminalize it and has the support of adat and religion to legitimize it. This study discusses the types of domestic violence and examples that occur against women and most of them may not even be considered violence. In addition, criminal regulations and laws are also ineffective, and they even exacerbate violence against women. The results suggest that legal weaknesses need to be addressed and eliminated, and that governments should be encouraged to comply with laws and change laws that are not appropriate. At the lower level, violence against women must be resolved socially by helping to grow women's NGOs, and thereby increasing women's awareness of their rights to violence.Keywords: domestic violence, criminology, domestic violence. AbstrakKekerasan terhadap perempuan adalah fenomena umum dan dimensinya meluas menyebabkan banyak kerugian pribadi dan sosial bagi suami istri, keluarga, dan masyarakat. Penelitian ini dilakukan dengan metode perpustakaan yang bertujuan untuk menyelidiki kekerasan terhadap perempuan di masyarakat Iran dengan pendekatan kriminologis. Banyak perempuan secara tradisional mendapat perlakua kekerasan atau tidak menyadari bahwa itu adalah tindak kekerasan, karena hukum tidak mengkriminalkannya dan mendapat dukungan adat dan agama untuk melegitimasinya. Dalam studi ini dibahas jenis kekerasan dalam rumah tangga dan contoh-contohnya yang terjadi terhadap perempuan dan sebagian besar bahkan mungkin tidak dianggap sebagai kekerasan. Selain itu, aturan-aturan dan hukum pidana juga tidak efektif, bahkan memperburuk kekerasan terhadap perempuan. Hasil penelitian menyatakan bahwa kelemahan hukum perlu ditangani dan dihilangkan, dan bahwa pemerintah harus didorong untuk mematuhi hukum dan mengubah hukum yang tidak sesuai. Di tingkat bawah, kekerasan terhadap perempuan harus diatasi secara sosial dengan membantu menumbuhkan LSM perempuan, dan dengan demikian dapat meningkatkan kesadaran perempuan tentang hak-hak mereka atas kekerasan.Kata kunci: KDRT, Kriminologi, Iran АннотацияНасилие в отношении женщин - обычное явление, и его широко распространенные масштабы причиняют множество личных и социальных потерь мужу и жене, семье и обществу. Это исследование было проведено с использованием библиотечного метода, целью которого является криминологическое исследование насилия в отношении женщин в иранском обществе. Многие женщины традиционно подвергались насилию или не осознают, что это акт насилия, потому что закон не криминализирует его и пользуется поддержкой адата и религии, чтобы узаконить его. В этом исследовании обсуждаются типы домашнего насилия и примеры, которые происходят в отношении женщин, и большинство из них можно даже не рассматривать как насилие. Кроме того, уголовные нормы и законы также неэффективны и даже усугубляют насилие в отношении женщин. Результаты показывают, что необходимо устранить и устранить слабые места в законодательстве, а также побудить правительства соблюдать законы и изменять законы, которые не подходят. На более низком уровне насилие в отношении женщин должно быть разрешено в социальном плане, помогая расти женским НПО и тем самым повышая осведомленность женщин об их правах на насилие.Ключевые Слова: домашнее насилие, криминология, Иран